Sociodemographic Contributions to Knowledge and Collaborative Communication Skills of Nurse Supervisors in Type C Hospital of West Sumatra - Yulyan Shari; Arif, Yulastri; Zifriyanthi Minanda Putri (LPPM Universitas Harapan Bangsa, 2024)
One crucial aspect of the professional development of nurse supervisors involves their sociodemographic characteristics, which can significantly impact their knowledge and skills in collaborative communication. This study aims to analyze the sociodemographic contributions of nurse supervisors to knowledge and collaborative communication skills, based on King’s Theory, within Type C Regional Hospitals in West Sumatra. The research methodology employed a crosstab-chisquare approach, with a sample consisting of 24 nurse supervisors. Supervisor education level showed a significant relationship with supervisor knowledge and skills (p < 0.05). The contribution of work period to supervisor knowledge and skills was also significant (p < 0.05. However, the age of the supervisor did not have a significant relationship with supervisor knowledge and skills with p>0.05. It is expected that hospital management can develop supervisor collaborative communication training based on King's theory on an ongoing basis focus on improving collaborative communication skills, especially for supervisors with shorter work periods or lower education levels.